Analisis Kendala Implementasi Pedoman Kendali Mutu Audit Aparat Pengawasan Intern Pemerintah Pada Inspektorat Daerah Kabupaten Bone Bolango - Utiarahman, Isran; Kalangi, Lintje; Manossoh, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. Audit Quality Control Guidelines for Government Internal Auditors (APIP) are procedures and controls that must be performed by each APIP institutions including policies, procedures and control program. The guidelines must be compiled by APIP to ensure that audits are conducted in accordance with the Audit Standards of APIP. There are eight elements in the Guidelines. Those are the Strategic Plan Formulation; Quality Control of Audit Planning of APIP, Audit Plan and Program, Audit Supervision, Audit Implementation, Audit Reporting, Follow-Up of Audit Findings, and Administration and Human Resources. The purpose of this study is to analyze the constraints in implementing PKMA-APIP in the Regional Inspectorate Bone Bolango. This study also discusses the strategies and efforts to overcome those constraints in order to provide assurance and ensure that audits are conducted in accordance with auditing standards APIP. This is a qualitative case study research. Data were obtained through indepth interviews, observation and documentation. Validity and reliability were determined by triangulation. Results show that the Regional Inspectorate Bolango Bone regency in implementing PKMA-APIP not fully in accordance with PERMENPAN and RB 19 Year 2009 on Guidelines for Audit Quality Control-APIP. Codes were established from the transcriptions. Findings indicate that PKMA-APIP was partially implemented. It is caused by some obstacles: organizational commitment, Integrity Auditor, Human Resources and inadequacy of Structure Bureaucracy. Efforts have been conducte to improve its human resources by training, implementing integrity, supporting, building committed leadership including all controllers and estabish the control procedures in accordance with PKMA-APIP.Â Keywords: Contraints, Quality Control, APIP.